PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSA PEMBELIAN KONSUMEN DI UD. SANRIS JAYA TELUKDALAM KABUPATEN NIAS SELATAN - Sadina Gee (Universitas Nias Raya, 2022)
The purpose of this study was to determine the effect of the promotion mix on consumers' purchasing decisions is UD. Sanris Jaya Telukdalam, South Nias Regency. The type of research used is a quantitative type. The source of the data was from consumers, with the population and sample in this study being as many as 32 respondents. Data collection techniques are research instruments or questionnaires. The results of this study showed that the calculated value was 6,050>table 1,703. This research can be concluded that there is a positive and significant influence of the promotional mix on consumers' purchasing decisions in UD. Sanris Jaya Telukdalam, South Nias Regency